A multi-stage approach for damage detection in structural systems based on flexibility. (August 2016) - Grande, E.; Imbimbo, M.
Abstract: The paper proposes a fusion approach for damage detection in structural applications in the case of multiple damage locations and three-dimensional systems. Based on the Dempster–Shafer evidence theory, a multi-stage approach is proposed with the mode shapes assumed as primary sources and local decisions based on a flexibility method. The proposed approach has been applied to two case studies, a a fixed end beam analyzed in other papers and a three dimensional structures codified in a Benchmark problem. Both the case studies have shown the ability and the efficiency of the proposed approach to detect damage also in the case of multiple damage, limited number of identified parameters and noise measurements. Highlights: A multi-stage approach for damage detection in structural applications is proposed. It combines the damage indicators based on flexibility approach with evidence theory. The approach performs very efficiently in the case of multiple damage scenarios. It is very efficient in 3D frames in case of limited number of identified parameters. It is stable also in presence of noise measurements.